Perancangan User Experience Aplikasi Pendaftaran Kunjungan Puskesmas Menggunakan Metode User Experience Lifecycle - Sita Widad Muqsithoh; Septi Andryana; Ira Diana Sholihati (SMATIKA JURNAL, 2022)
The health sector is one of the important sectors of the government which has the potential to be improved by the presence of information technology. The public health center of East Ciputat District, which is one of the health service centers in the South Tangerang City, always improves the technology development. The large number of patient visits it causes problems with queuing visits which take a relatively long time when registering at the service counter. The advantage of the User Experience Lifecycle method that is applied to the development process of the mobile public health center visit online registration application starts from the analysis stage that understands user needs through the data collection method. The design stage involves making Wireframe. The design results are implemented in the form of a mobile based High-Fidelity Prototype and the results are tested using the System Usability Scale (SUS). The prototype evaluation can show the overall results of the application successfully helping users in the efficiency of online registration visitors.